The processability evaluation of composite of ships and floating structures based on system-technical approach - Казимиренко, Юлия Алексеевна; Савочкина, Вера Владимировна (Technology audit and production reserves, 2015)
The article discusses the indicators of design manufacturability of biological protection of ships and floating structures for the transportation and storage of radioactive cargo of low and medium activity. The new metal-glass electric-arc coatings and aluminum-matrix hot-pressed tiles are proposed for protective layers of structure production, cladding being is carried out with epoxy adhesive. In order to select the variant of the design which corresponds to the technological and economic indicators of efficiency, the systematic and technical approach based on the detailed complex technological indicators has been used. The coefficients of material capacity, design complexity, manufacturability of materials have been selected as the proper criteria. The detailed characteristics of technical and economic indicators of manufacturing structures of biological protection have been considered and the nomogram for determining complex coefficient of manufacturability with different types of composite protective layers was built. The influence of material and coating composition on the factor of material capacity has also been detected. The determination of the complex coefficient of design manufacturability for different design and layout solutions will allow to develop organizational and technical activities and predict the dynamics of the formation of the factors of economic efficiency. The results can be used at the stages of design studies, technological preparation of manufacture, construction and operation of ships and floating structures.